Even three-year-old children know that the source of enlightenment is not religion but science: modern Japanese Buddhism between ‘Religion’ and ‘Science’ 1860s-1910s - Krämer, Hans Martin (Journal of Religion in Japan, 2019)
When Japanese Buddhists faced the challenge of materialistic natural sciences in the last decades of the nineteenth century, their responses were not uniform. Some advocated a unity of science and religion in the sense that Buddhism was thought to be substantially compatible with the findings of modern natural science, while others argued for a separation of domains, salvaging for religion a sphere of life that would remain unaffected by modern rationalist forms of critique. Yet, both sides already argued from within a logic of the secular/non-secular, thus showing that, next to political demands, the challenges posed by modern science were an important catalyst for the emergence of expressions of secularity in modern Japan. This article attempts to make sense of the diverse Buddhist self-articulations vis-à-vis modern science by differentiating chronologically, by sect, and by addressee, thus seeking out patterns to explain the contemporaneity of opposing positions within Japanese Buddhism.